Antiretroviral Therapy Complications and Their Correction in HIV-Infected Pregnant Women in the Perioperative Period - E. M. Shifman; V. Ya. Vartanov; N. N. Khutorskaya; L. V. Krugova (Общая реаниматология)
The review gives information on the specific features of a perioperative period in HIV-infected patients receiving anti-retroviral therapy. The possible complications resulting from the use of antiretroviral drugs and their correction modes are described.